Evaluation of Next-Generation Sequencing to Investigate the Epidemiology of Clostridioides difficile Infection - Moloney, Geraldine (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2022)
Introduction: Clostridioides difficile (C. difficile) is an anaerobic bacteria, which can cause gastrointestinal infection. There are approximately 2,000 cases of C. difficile infection (CDI) diagnosed in Ireland per year, mostly in hospitalised patients. Risk factors for CDI include antibiotics and proton-pump inhibitor medication. These medications may alter a person’s normal intestinal flora, the intestinal microbiome, sufficiently to allow CDI as a secondary infection. Recurrence of CDI (RCDI) can affect 20-40% of patients. CDI can also affect people who have not been admitted to hospital, known as community-acquired CDI (CA CDI). C. difficile has also gained recognition as a veterinary pathogen in recent years. As CDI has become such an important issue in healthcare, techniques were developed to identify isolates which may be related to each other, and identify potential transmissions. These techniques include PCR ribotype analysis of a specific genetic sequence and next-generation sequence (NGS) analysis of C. difficile genomes. NGS analysis can also be used to identify the microbiome composition of a sample, by the content and diversity of 16S rRNA fragments, known as amplicons. This can reveal the presence or absence of other bacteria, which can influence the development and/or the recurrence of CDI. Methods: A prospective observational cohort study was conducted in St James’s Hospital over a 3-year period. During this time, C. difficile isolates were cultured from the faecal samples submitted to the diagnostic laboratory and had a positive PCR result for the C. difficile toxin B gene. Additional isolates of CA CDI, and veterinary isolates were obtained. All isolates were subject to PCR ribotype and NGS analysis. The medical notes of inpatients with CDI were reviewed for clinical variables, symptomatic status and CDI management. Epidemiological details were integrated with ribotype and genome findings, to identify possible transmissions. Faecal samples were also used to generate microbiome profiles by 16S amplicon sequencing, to investigate bacterial markers predictive of RCDI. Results: There were 335 clinical and 20 porcine C. difficile genomes analysed by NGS. By the similarities (0-2 SNPs) found between isolates, a transmission rate of 21% was identified for this study. Transmissions were most often seen in older patients, under the care of the same clinical staff. There were significant differences between the antibiotics preceding CDI diagnosis and those of all hospital inpatients, which may account for the identified distribution of C. difficile ribotypes. As ribotype 078 was most common among clinical and porcine isolates and common in the CA CDI isolates, an additional analysis of these isolates was undertaken. This identified further genomic similarities between these and the ribotype 078 isolates of a European study of nosocomial CDI and a Dutch investigation of farm and clinical isolates. An outbreak of a unique sequence type of C. difficile was recognised, involving SJH and a local hostel. Microbiome analysis was completed for 70 samples, and found similar measures of overall bacterial richness. However, certain bacterial species were significantly lower in the samples pertaining to RCDI. These species have been investigated elsewhere for potential use as probiotics. Conclusions: The application of NGS analysis of C. difficile genomes and faecal microbiome samples provides much greater insight to the epidemiology of CDI and recurrence than what was previously understood.
Keywords: Clostridioides difficile; sequence analysis; ribotyping; molecular epidemiology; genomics; one health; microbiota; dysbiosis